2005
DOI: 10.1074/jbc.m409931200
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutagenesis and Kinetic Studies of the West Nile Virus NS3 Protease Identify Key Enzyme-Substrate Interactions

Abstract: The flavivirus West Nile virus (WNV) has spread rapidly throughout the world in recent years causing fever, meningitis, encephalitis, and fatalities. Because the viral protease NS2B/NS3 is essential for replication, it is attracting attention as a potential therapeutic target, although there are currently no antiviral inhibitors for any flavivirus. This paper focuses on elucidating interactions between a hexapeptide substrate (Ac-KPGLKRp-nitroanilide) and residues at S1 and S2 in the active site of WNV proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 37 publications
3
64
1
Order By: Relevance
“…Our results support and extend the previous findings of several groups (6,7,10,19,20,23,24,26,36) and also provide a structural rationale for the reduced selectivity of the DV proteinase, which tolerates well the presence of a number of amino acid residue types at both P1Ј and P2Ј positions. Importantly, earlier studies did not determine any significant difference in the P1Ј or P2Ј specificity between the WNV and DV enzymes (6,7,20).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results support and extend the previous findings of several groups (6,7,10,19,20,23,24,26,36) and also provide a structural rationale for the reduced selectivity of the DV proteinase, which tolerates well the presence of a number of amino acid residue types at both P1Ј and P2Ј positions. Importantly, earlier studies did not determine any significant difference in the P1Ј or P2Ј specificity between the WNV and DV enzymes (6,7,20).…”
Section: Discussionsupporting
confidence: 81%
“…Full-length NS3 is a bifunctional protein: its N-terminal and C-terminal portions encode the NS3pro domain and the helicase (NS3hel) domain, respectively (33,35). NS3pro is responsible for cleavage of the capsid protein C, as well as the boundaries between NS2A/NS2B, NS2B/NS3, NS3/NS4A, NS4A/ NS4B, and NS4B/NS5 (6,24).…”
mentioning
confidence: 99%
“…2A). Accordingly, in WNV or DV proteases, mutation of Asp129 to Glu (which may be too long) or Ala (which cannot saltbridge) abrogates catalysis (Chappell et al 2005). In trypsin, Asp189 plays an analogous role (Perona and Craik 1995;Hedstrom 2002), consistent with its similar P1 specificity.…”
Section: Substrate Specificity Of the Flavivirusesmentioning
confidence: 79%
“…Previous studies showed that the presence of the 48 residue central NS2B domain linked to the N-terminus of NS3 significantly enhanced the accumulation of soluble recombinant NS3pro in E.coli [18,20,23]. We used a similar approach to express the WNV NS2B-NS3pro.…”
Section: Resultsmentioning
confidence: 99%